Night of the ninjas - Osborne, Mary Pope; Dyanmo design (London Fox red, 2022)
Jack and Annie's adventures have started again, they're stuck in ancient Japan, where the shadowy ninjas and the fierce Samurai warriors don't look very friendly, will Jack and Annie find the tree house again? or will they be caught in a terrifying battle?
English stories
Keywords: English fictions